Transformasi Komunikasi Dakwah dalam Era Digital: Peluang dan Tantangan dalam Pendidikan Islam Kontemporer - Samsul Rani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This study aims to examine the transformation of da'wah communication in the digital era and identify opportunities and challenges faced in the context of contemporary Islamic education. By studying communication theory, information technology, and Islamic education, this research focuses on the impact of changing times marked by advances in information and communication technology. The research method uses a qualitative approach, with literature studies, interviews, and observation as data collection techniques. Through analysis of the latest data and literature, this research finds that the digital era has opened up opportunities for access to information and a wider global reach for Islamic da'wah through various social media platforms and other digital technologies. However, challenges that arise, such as the risk of content not by religious teachings and the digital divide among Muslims, are a serious concern in efforts to spread religious messages wisely. Therefore, this study highlights the importance of a religious values-based approach in integrating technology into contemporary Islamic education so that da'wah can be carried out effectively and consistently with prevailing religious principles. The results of this study conclude that it is important to provide valuable insights for preachers and practitioners of Islamic education in taking advantage of opportunities in the digital era as well as overcoming challenges that arise to optimize the transformation of da'wah communications and carry out Islamic education that is adaptive in the midst of changing times.